Pathogenic Factors Correlate With Antimicrobial Resistance Among Clinical Proteus mirabilis Strains - Filipiak, Aneta; Chrapek, Magdalena; Literacka, Elżbieta; Wawszczak, Monika; Głuszek, Stanisław; Majchrzak, Michał; Wróbel, Grzegorz; Łysek-Gładysińska, Małgorzata; Gniadkowski, Marek; Adamus-Białek, Wioletta (Frontiers in Microbiology, 2020)
Proteus mirabilis is the third most common etiological factor of the urinary tract infection (UTI). It produces urease, which contributes to the formation of crystalline biofilm, considered to be one of the most important virulence factors of P. mirabilis strains, along with their ability to swarm on a solid surface. The aim of this study was to analyze the pathogenic properties of two selected groups of clinical P. mirabilis isolates, antimicrobial-susceptible and multidrug-resistant (MDR), collected from hospitals in different regions in Poland. The strains were examined based on virulence gene profiles, urease and hemolysin production, biofilm formation, and swarming properties. Additionally, the strains were characterized based on the Dienes test and antibiotic susceptibility patterns. It turned out that the MDR strains exhibited kinship more often than susceptible ones. The strains which were able to form stronger biofilm had broader antimicrobial resistance profiles. It was also found that the strongest swarming motility correlated with susceptibility to most antibiotics. The correlations described in this work encourage further investigation of the mechanisms of pathogenicity of P. mirabilis.